Determining Factors Affecting International Students' Satisfaction among Iranian Medical Sciences Universities: A Qualitative Study - Kobra Nakhoda; MohammadAli Hosseini; Kamran Mohammadkhani; Nader gholi Ghorchiyan (Zanjan University of Medical Sciences and Health Services, 2020)
Background & Objective Given the growing global competition between countries and universities to attract international students, determining the level of satisfaction of these individuals and factors involved in their dissatisfaction during the admission and attraction processes is of utmost importance. Therefore, this study aimed to identify the factors affecting the satisfaction of international students who are studying in medical Universities in Tehran, Iran. Materials and Methods: This qualitative research was performed with a conventional content analysis approach. Up to data saturation, 17 participants were selected from the international students of three universities in the second semester of the academic year of 2018-2019. The subjects were selected by purposeful sampling considering maximum diversity. In addition, data were collected via individual semi-structured interviews and simultaneously analyzed based on Graneheim and Lundman analysis method. Results The interviews were classified in more than 680 open codes, six categories, and 25 subcategories. According to the results, the main factors for dissatisfaction of international medical students included low language proficiency, lack of financial support, weaknesses in academic-educational and managerial processes, and weaknesses in counseling and information processes, welfare problems and improper encounters and interactions. Conclusion: According to the results of the study, it is suggested that more attention be paid to the mentioned factors by higher education policymakers and managers and attempts be made to eliminate these challenges in order to strengthen the system of attracting international students and achieving a high position at the regional and global levels in this respect.